Numerical and experimental study of primary drying stage in freeze-drying of Cordyceps militaris - Nguyen, Phuc V; Nguyen, An N (Edelweiss Applied Science and Technology, 2025)
This study develops a mathematical model to simulate the heat and mass transfer processes during the freeze-drying of cylindrical biological materials, with Cordyceps militaris fibers serving as the representative case. The model accounts for the coupled mechanisms of heat conduction and vapor diffusion within the porous structure. A one-dimensional system of partial differential equations is established and solved using the finite difference method implemented in MATLAB. The simulation outputs include the temporal evolution of surface temperature, dry region temperature, moisture content, internal energy, and the position of the sublimation front. Model validation was conducted through experimental comparison, yielding average percentage errors of 0.98% for temperature, 7.12% for moisture ratio, and 6.24% for drying time, resulting in an overall error of 5.5%. These results confirm the model’s reliability in capturing key drying dynamics. The study concludes that accurate modeling of coupled heat and mass transfer is essential for predicting freeze-drying behavior. The findings offer a theoretical foundation for optimizing freeze-drying protocols for Cordyceps militaris and similar cylindrical structures, contributing to improved energy efficiency and product quality in practical applications.